CUPS-SSI: IMPROVING CONCEPTUAL UNDERSTANDING THROUGH INTEGRATION COOPERATIVE LEARNING MODEL WITH SOCIAL SCIENTIFIC ISSUES - Rahman, Nurul Aulia; Nur Abu, St. Hayatun; Hamzah, Eka Fitriana; Gustiana, Gustiana; Sari, Nur Indah (Universitas Negeri Makassar, 2024)
This study aims to design a CUPs-SSI learning model that meets the criteria of valid, practical, and effective in improving students' understanding of chemical concepts. The resulting learning model is a cooperative learning model oriented to the application of social science issues in education. The type of research is R&D (research and development), with the design of the Plom development model. Data collection techniques use tests and non-tests. After going through the design, realization of design, and validation stages, the CUPs-SSI (conceptual understanding procedures oriented to socio scientific issues) learning model was produced which has six syntax or stages of learning, namely investigation, exploration, hypothesis, verification, presentation, and generalization. Other components of the CUPs-SSI learning model consist of social systems, reaction principles, support systems, instructional impacts, and herding impacts. The results of the limited trial of the conceptual understanding test of students after learning with the CUPs-SSI model, were in the good category with an average percentage of 85.11%. Thus, theoretically, this research shows that the CUPs-SSI model, can improve students conceptual understanding. Practically, the research results show that the CUPs-SSI model is suitable for use as an alternative learning model, especially for science material.